2016
DOI: 10.1002/ecs2.1520
|View full text |Cite
|
Sign up to set email alerts
|

Variation in plant‐mediated intra‐ and interspecific interactions among insect herbivores: effects of host genotype

Abstract: Abstract. Many studies show that indirect interactions between insect herbivores via shared host plants are common and often mediated by plant-induced responses to damage. However, we lack some types of data that will be needed to model how plant-mediated interactions on individual plants contribute to the population dynamics of interacting herbivores. Specifically, there are few simultaneous characterizations of both the intra-and interspecific effects that are mediated by the host plant, as well as host plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 71 publications
(124 reference statements)
2
10
0
Order By: Relevance
“…(Ortego et al., ) and were associated with reduced larval growth on multiple genotypes in our experiment. Second, in a previous study, we found that previous L. juncta larval damage to S. carolinense , at levels within the range of this experiment, significantly reduced the growth of conspecifics feeding on undamaged, isolated leaves on the same plant (McNutt & Underwood, ). Importantly, in these previous experiments, damaging larvae did not have access to leaves used for bioassays, so these negative effects on growth were unambiguously indirect and mediated by host plant systemic induced resistance.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…(Ortego et al., ) and were associated with reduced larval growth on multiple genotypes in our experiment. Second, in a previous study, we found that previous L. juncta larval damage to S. carolinense , at levels within the range of this experiment, significantly reduced the growth of conspecifics feeding on undamaged, isolated leaves on the same plant (McNutt & Underwood, ). Importantly, in these previous experiments, damaging larvae did not have access to leaves used for bioassays, so these negative effects on growth were unambiguously indirect and mediated by host plant systemic induced resistance.…”
Section: Discussionsupporting
confidence: 55%
“…Our study is consistent with the interpretation that reducing oviposition on damaged plants may help L. juncta to avoid exposing their offspring to plant induced responses that affect larval growth. Although the effects of larval density on larval performance were not particularly strong in this experiment, we have previously found that S. carolinense induced resistance to L. juncta damage can reduce larval growth by up to 42% over 48 h of feeding (McNutt & Underwood, ). The avoidance of damaged plants by L. juncta females may also be adaptive for other reasons.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…For example, conspecific pre-infestation increased the number of nymphs produced by Myzus persicae [ 9 ], while Bemisia tabaci pre-infestation reduced M. persicae fecundity [ 1 ]. Nevertheless, few studies have simultaneously investigated both intra- and inter-specific effects mediated by the same host plant [ 10 ]. Furthermore, while plant-mediated interactions between herbivorous insects have been widely reported for herbaceous plants, similar studies on woody plants have been largely overlooked.…”
Section: Introductionmentioning
confidence: 99%